Museums University as Catalysts for Islamic Cultural Heritage Preservation and Learning Laboratories - Azwar, Muhammad; Purnomo, Pungki; Farida, Ida; Fadhillah, Amir (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2025)
As a pioneer of university museums among state Islamic universities in Indonesia, the UIN Malang and UIN Banda Aceh museums play a vital role as role models for other UINs in managing and empowering university museums as important units in higher education institutions. The purpose of this study is to discuss the UIN Malang and Banda Aceh museums in playing a role as preservation institutions of cultural heritage and a learning laboratory in organizing learning activities for academics and the community outside the campus. By using a qualitative approach and case study method, data collection techniques are observation, in-depth interviews with museum managers and academics. Data analysis is carried out by reducing data, presenting data and drawing conclusions. The findings of the study show that the academics and the community engagement is not as an object in preserving the cultural heritage of Islam and Indonesia. Academics, community leaders and community groups jointly play an active role in carrying out conservation activities. The same thing is also done by museum managers by involving academics and the community to discuss the implementation of educational activities that are needed by themselves such as exhibitions, training, workshops, and seminars. This study confirms the importance of university museums and can form a creative and innovative academic culture among academicians and community.